Thermodynamic and kinetic characterization of methane hydrate ‘nucleation, growth and dissociation processes, according to the labile Cluster theory - Alberto Maria Gambelli; Federico Rossi (Chemical Engineering Journal, 2021)
Methane hydrates were formed and then dissociated in presence of fresh water and a pure quartz porous medium, by using a small-scale experimental apparatus, appositely designed for those experiments. The most significant phases describing the process, or nucleation, massive growth and dissociation, were characterized both thermodynamically and kinetically. Methane hydrate equilibrium was defined in presence of such porous medium and the hydrate formation rate was calculated for kinetic considerations. To do this, the Labile Clusters Theory was considered and, according to it, hydrate formation was considered a first-order chemical kinetic equation for the time dependence. Finally, pressure variation over time was discussed. The comparison between trend assumed by those parameters revealed consistent and visible similarities, which allowed to a very deepened characterization about all three phases making up the whole process.